Effects of dietary genistein on nutrient use and mineral status in heat-stressed quail. - Şahin, Kazım; Şahin, Nurhan; Onderci, M; Sarkar, FF; Prasad, A; Doerge, D; Küçük, Ömer (Amer Inst Nutrition, 2004)
[Abstract Not Available]
5th International Symposium on the Role of Soy in Preventing and Treating Chronic Disease -- SEP 21-24, 2003 -- Orlando, FL